Financial instruments disclosure practices: evidence from Malaysian listed firms - Syaima' Adznan; Sherliza Puat Nelson (Fakulti Ekonomi dan Pengurusan, 2015)
The current changes in business settings have directed companies to conduct businesses at the international level which requires the use of financial instruments. The mandatory MFRS 7, an adoption of IFRS 7 standard has been implemented for entities to disclose their involvement with financial instruments. Thus, the aim of this study is to investigate the financial instruments disclosure practices (FID) among Malaysian listed companies; specifically, on the level of compliance with MFRS 7. The overall results indicate that companies complied with MFRS 7, though there are several requirements omitted by companies. Furthermore, with the revision of Malaysian Code of Corporate Governance (MCCG) in 2012, this study examines the association of corporate governance mechanisms (board expertise, audit committee independence, audit fee, external and internal audit functions) with the extent of FID among companies. Based on a total sample of 319 Malaysian public listed companies for financial year end 2012, the analysis reveals that FID is significantly and positively associated with audit committee independence and external audit functions, while internal audit is negatively associated. Hence, it suggests that effective corporate governance is crucial as this is likely to have some influence on the extent of disclosure level among companies.